2021
DOI: 10.1177/21582440211013779
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Collaborative Supervision Approaches and Collegial Supervision Techniques on Teacher Intensity Using Performance-Based Learning

Abstract: This study aims to examine the effect of collaborative supervision approaches and collegial supervision techniques on teacher intensity using performance-based learning in the learning process. In addition, its purpose is also to examine the impact on student learning outcomes. This study was conducted in East Java, Indonesia, with a descriptive correlational research design. The research samples were obtained in three cities, namely Malang, Blitar, and Batu, with a total sample of 146 primary education teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The higher the teacher’s work motivation is, the higher their performance is. Thus, it can be concluded that the results of this study support the results of the previous studies about work motivation which has a positive effect on employee work performance ( Wiyono et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The higher the teacher’s work motivation is, the higher their performance is. Thus, it can be concluded that the results of this study support the results of the previous studies about work motivation which has a positive effect on employee work performance ( Wiyono et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…There is a significant positive relationship between several supervision techniques and teacher performance [6]. The frequency of collegial supervision techniques using a collaborative approach affects the performance-based learning that is applied by teachers [37]. The implementation of clinical supervision can also improve teachers' teaching performance [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several research results have shown that collegial supervision is effective in improving teaching competence [8]. Collegial discussion is the most common form of collegial supervision carried out by teachers.…”
Section: Collegial Discussion As An Instructional Supervision Techniquementioning
confidence: 99%
“…The findings of this study are related to the results of previous studies that a supervisory approach using a collaborative approach can improve the teaching competence of the teachers. Collegial supervision techniques are effective in improving teaching competence as well [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation